A case report of parenchymal hematoma after intravenous thrombolysis in a rivaroxaban-treated patient: Is it a true rivaroxaban hemorrhagic complication?. Issue 51 (December 2017) - Rota, Eugenia; Bruzzone, Gianluca; Agosti, Sergio; Pastorino, Roberto; Morelli, Nicola
Abstract: Rationale: To date, the only treatment approved for acute ischemic strokes is thrombolysis. Whether intravenous thrombolysis may be safe in patients taking direct oral anticoagulants (DOACs) is currently a matter of debate. Patient concerns: A 74-year-old woman, who was on rivaroxaban 20 mg/d for nonvalvular atrial fibrillation, was admitted to our stroke unit with left-sided hemiparesis and aphasia. The onset of neurologic deficits had occurred 5 hours after the last rivaroxaban dose. Diagnosis: An acute ischemic stroke was diagnosed. Interventions: The patient was administered thrombolytic treatment with intravenous recombinant tissue plasminogen activator (r-TPA) 3 hours and 20 minutes after symptoms onset. Seven hours post-r-TPA treatment, the neurological deficit had worsened, and a type I intraparenchymal hematoma was detected on a computed tomography brain scan. Outcomes: The clinical/neuroradiological picture improved significantly in the following days. The patient was discharged to a rehabilitation facility after 3 weeks. Lessons: In this case, factor ten activated (Xa) inhibitor, rivaroxaban might have increased the risk of hemorrhagic transformation of the ischemic stroke. However, this risk was overweighed by the benefit of thrombolysis, as the patient's clinical condition had improved significantly in the following weeks. The current guidelines discourage the use of thrombolytic treatment in patients with DOACs administered within the last 24(48) hours. However, the case reported herein and other world experiences, even though limited, suggest that an ongoing DOAC medication could no longer be considered a barrier to r-TPA treatment which may be a reasonable and valuable option, at least in selected acute stroke patients taking factor Xa inhibitors.